Correlating hydrodynamic radii with that of two-dimensional nanoparticles - Yue, Yuan; Kan, Yuwei; Choi, Hyunho; Clearfield, Abraham; Liang, Hong (Applied physics letters, 2015)
Dynamic light scattering (DLS) is one of the most adapted methods to measure the size of nanoparticles, as referred to the hydrodynamic radii (Rh). However, the Rh represents only that of three-dimensional spherical nanoparticles. In the present research, the size of two-dimensional (2D) nanoparticles of yttrium oxide (Y2O3) and zirconium phosphate (ZrP) was evaluated through comparing their hydrodynamic diameters via DLS with lateral sizes obtained using scanning and transmission electron microscopy. We demonstrate that the hydrodynamic radii are correlated with the lateral sizes of both square and circle shaped 2D nanoparticles. Two proportional coefficients, i.e., correcting factors, are proposed for the Brownian motion status of 2D nanoparticles. The correction is possible by simplifying the calculation of integrals in the case of small thickness approximation. The correcting factor has great significance for investigating the translational diffusion behavior of 2D nanoparticles in a liquid and in effective and low-cost measurement in terms of size and morphology of shape-specific nanoparticles.